Barometric Pumping Through Fractured Rock: A Mechanism for Venting Deep Methane to Mars' Atmosphere. Issue 14 (20th July 2022) - Ortiz, J. P.; Rajaram, H.; Stauffer, P. H.; Harp, D. R.; Wiens, R. C.; Lewis, K. W.
Abstract: Both the source of methane on Mars and the mechanism for transmission from the subsurface to the atmosphere are not fully understood. Previous seepage simulations have invoked relatively shallow subsurface sources to explain observed methane signatures on Mars. We propose that barometric‐pressure pumping through fracture networks could be an effective mechanism for methane transport from the deep subsurface on Mars. Using atmospheric pressure data gathered by Curiosity as input, we simulate methane gas transport from depths of 200 m to the surface. Even with such a deep source, our model reproduces the observed seasonality of methane, and the simulated surface methane fluxes fall within the range of previous estimates derived from atmospheric observations. Because 200 m is the likely minimum hospitable depth for living methanogenic microbes, our fracture network model indirectly reinvigorates the possibility of a microbial source of methane on Mars. Plain Language Summary: The existence of methane on Mars is a topic of significant interest because of its potential association with subsurface microbial life. Measurements of methane in the atmosphere of Mars indicate that its abundance fluctuates over time. Although the source of methane is unknown, it most likely comes from below the surface of Mars; however, the range of depths of potential methane sources is not well constrained. If methane is currently being produced by living microbes, it would have to be at depths of at least 200 m in order to support life. Nearly all prior modeling work in this area has considered relatively slow, inefficient methane transport mechanisms, which limits the methane sources to the shallow martian subsurface. In this paper, we describe and model a mechanism capable of transporting significant quantities of methane to the atmosphere from depths capable of supporting living methane‐producing microorganisms. We also find that the methane seepage pattern generated by our model is highly seasonal, and closely follows the pattern of atmospheric methane concentrations measured by the Curiosity rover. Key Points: Atmospheric pressure fluctuations on Mars can produce significant methane seepage from potentially habitable depths (up to 200 m) Modeled surface methane seepage patterns are highly seasonal and coincide with rover measurements of elevated concentrations at Gale crater Magnitude and timing of modeled surface flux is comparable to existing plume estimates, supporting a model of localized surface releases